The role of local wisdom in preventing adolescent risk behaviors based on safe communities safe schools in Banda Aceh - Renaldi, Teuku; Syukri, Maimun; Oktari, Rina S.; Nurjannah, Nurjannah (Trends in Infection and Global Health, 2024)
Adolescent risk behavior is a public health problem that occurs globally. The presence of the digital era is characterized by increased access to online content and contributes to the rise of risk behavior among teenagers. The Center for Study and Prevention of Violence (CSPV) at the University of Colorado, United States has developed the concept of Safe Communities Safe Schools (SCSS) as a model for preventing adolescent risk behavior in Colorado. The development of the current situation in Indonesia, especially in Banda Aceh, has given rise to the need for an equivalent concept in Banda Aceh. Adaptation and implementation of the SCSS concept from Colorado to Banda Aceh require adjustments that accommodate cultural components, including local wisdom. The aim of this study was to examine the role of local wisdom in supporting the implementation of SCSS as prevention of risk behavior among adolescents in Banda Aceh. This research uses a qualitative design with a grounded theory approach. Data collection was carried out through in-depth interviews with key informants, namely Acehnese special institutions which officially represent expertise in local wisdom in the City of Banda Aceh. These institutions are: the Regional Education Council (MPD), Aceh Tradition Council (MAA), and Banda Aceh City Ulama Council (MPU). Data analysis was carried out using applied thematic analysis. This research identifies local wisdom sourced from Islamic law, which is a cultural characteristic of the Acehnese people and has the potential to play a role in supporting the implementation of SCSS. The local wisdoms are: education in Islamic values, akhlakul karimah, special relationships between teachers and parents of students (takzim keu guree), and traditional gampong governance. The Banda Aceh City Government has implemented local wisdom education on Islamic values, including akhlakul karimah through the diniyah program in schools. Traditional gampong governance can play its role through two mechanisms: revitalizing the local wisdom of takzim keu guree through community development targeting students' parents and reviving the local wisdom of akhlakul karimah in the community targeting students and families. Local wisdom implemented through the diniyah program is in line with the implementation of SCSS in schools, and local wisdom of traditional gampong governance and takzim keu guree can be a form of support for SCSS from the community. This support can be realized considering that Sharia law and traditional gampong governance have received legal regulation for their implementation in the City of Banda Aceh. Banda Aceh's local wisdom originating from Islamic law can play a role in supporting the implementation of SCSS as a prevention of risk behavior among teenagers in Banda Aceh. This research recommends utilizing local wisdom of Sharia law and gampong governance through regulatory mechanisms and cross-sectoral cooperation.